The sustainability of vegetable oils and butters production in na amazonian community – RESEX Médio Juruá (Research, Society and Development, 2021)
It is increasingly evident the importance of the economic use of the diversity of forest products, among them the Non Timber Forest Products. The aggregation of values, the use of adequate technologies to the exploitation conditions, sustainable forest management and the development of appropriate research, converge in a more strategic plan in the restructuring of the commercialization of these vegetable inputs. In this work the production process of vegetable oils and butters in the Amazon is analyzed with a view to sustainability. For this, a case study was carried out at the Oil Extraction Industry of the Roque Community, located in the municipality of Carauari, Amazonas, based on the analysis of the environmental dimension of the production process complemented by theoretical review, research and descriptive analysis. The parameters analyzed in this process were the management of native vegetation, the use of raw materials and the destination of residues. Currently, the seeds processed in the industry are of the Andiroba, Murumuru and Ucuúba species, collected in 51 communities in the Médio Juruá Territory. It was observed that the yield in the industrial process of the seeds rarely exceeds 30%, 23% and 43% respectively, of the total volume of processed seeds, which generates large amounts of waste. The biggest costs for the production of oil and butters are the acquisition of raw materials and distribution logistics. Besides these difficulties, the producers still deal with the seasonality of the production of forest species, which in some years yields more raw material and in others not, consequently impacting the earnings of the Cooperative responsible for managing the industry.